Improving Ability to Recognize Hijaiyah Letters through Flash Cards in Early Childhood - Duwi Meilina (Journal of Childhood Development, 2022)
This research explores the effort to enhance Arabic letter recognition using Flash Cards among early childhood learners at RA Nurul Iman in Tanjung Bulan Village, Kasui District, Way Kanan Regency, Lampung. The findings clearly demonstrate the positive impact of the flash card media on hijaiyah letter recognition within Group B children. The overall average percentage gain of 70.46% aligned with the "Developing As Expected" (BSH) criteria underscores the efficacy of the flash card media in this context. The research suggests practical implications for both educational institutions and parents. Schools are advised to integrate flash card media across various relevant learning themes to optimize its benefits. Additionally, parents are encouraged to actively participate in supporting and guiding their children's hijaiyah letter recognition practice at home. As a concluding recommendation, future research endeavors could delve into comparative studies assessing hijaiyah letter recognition abilities facilitated by flash card media across diverse scenarios or conditions. Such research could provide a more comprehensive understanding of the versatility and generalizability of this instructional approach.